If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 13 = -25 Reorder the terms: 13 + x = -25 Solving 13 + x = -25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + x = -25 + -13 Combine like terms: 13 + -13 = 0 0 + x = -25 + -13 x = -25 + -13 Combine like terms: -25 + -13 = -38 x = -38 Simplifying x = -38
| 11x-9+5x+5=190 | | 2x-2(-5x+14)=2 | | 5x+1-4x=-4 | | 2x+5-1=6 | | -5*s-13=-68 | | x-25=-9 | | -94x-76=-94-23x | | 4x=5+3.8*x | | 3(x+4)+1=31 | | 0.15(x+50)-0.04(x-20)=2.8 | | -6g+3(-7+4g)=1-g | | 2.5x+9=209+.5x | | 6w+48=48 | | -20=-4-(6x) | | y=-2/3(-1)+1 | | y=-2/3(1)+1 | | 2u=-8 | | z-0.5=0.25z-0.125 | | U-9.9=4.99 | | y=-2/3(0)+1 | | 9(4x+8)=12(12+3x) | | h=-16t^2+1000 | | 32=6(x+4)-8x | | (3x+4)+(2x+2)= | | 8+5(7+5n)=193 | | 2.5x+1.96=1.7x+2.92 | | w+6-13=-27 | | 3(5x+4)=31 | | 3x+2(5)=0.2(2y+1) | | 45+5.50x=195+4.25x | | -x+3(-x+8)=0 | | 3+4+a=12 |